2018
DOI: 10.4274/tjod.55492
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy in the Dubai health system: A fifteen year experience

Abstract: Objective:To determine the incidence, demographic data, risk factors, indications, outcome and complications of emergency peripartum hysterectomy (EPH) performed in two major tertiary care hospitals in Dubai, and to compare the results with the literature.Materials and Methods:The records of all women who underwent EPH from January 2000 to December 2015 in two major tertiary care hospitals in Dubai were accessed and reviewed. Maternal characteristics, hysterectomy indications, outcomes, and postoperative compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A recent publication by Tahlak et al showed that the CS rate has increased in the past 15 years from 1 in every 5 births to 1 in every 3 births. 11 New insurance policies have encouraged the private sectors to develop a more sophisticated management that may be associated with an increase in health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication by Tahlak et al showed that the CS rate has increased in the past 15 years from 1 in every 5 births to 1 in every 3 births. 11 New insurance policies have encouraged the private sectors to develop a more sophisticated management that may be associated with an increase in health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…The main indications for emergency obstetric hysterectomy are placental abnormalities, uterine weakness, and uterine rupture. 6 , 7 Obstetric emergency hysterectomy can be subdivided into total hysterectomy and subtotal hysterectomy. Although the pros and cons of the two techniques have been investigated, whether subtotal hysterectomy should be performed prior to total hysterectomy remains controversial.…”
Section: Introductionmentioning
confidence: 99%